Intestinal obstruction. Issue 3 (March 2017) - Griffiths, Shelly; Glancy, Damian G.
Abstract: Intestinal obstruction is a common surgical emergency, accounting for up to 20% of admissions with acute abdominal pain. Of these, 80% will have small bowel obstruction, the most common cause being adhesions. Colorectal cancer is the most common cause of large bowel obstruction. The cardinal features of obstruction are abdominal pain, vomiting, distension and absolute constipation. Initial management comprises adequate fluid resuscitation, decompression with a nasogastric tube and early identification of strangulation (signs of which may include tachycardia, tenderness, fever and leucocytosis) requiring operative intervention. Appropriate use of contrast imaging can differentiate between patients that are likely to settle conservatively and those that will require surgery.